Alternatif Bersuci Antara Berwudhu dan Tayamum Dalam Al-Qur’an - Aulia Santri Agustin; Aflah Akhwan (Yayasan Bayt Shufiya Nusantara, 2025)
This paper aims to describe the concept of ablution and tayamum as stated in the Qur'an, especially in surah Al-Maidah verse 6. This research uses a qualitative method with a thematic interpretation approach as an analytical knife. The data is obtained through literature study with the main source in the form of the Qur'an and books of tafsir, and supported by secondary data derived from books, scientific journals, and relevant theses. The results show that the Qur'an provides clear and systematic guidance on the procedures for purification, both through ablution and tayamum, as a valid requirement in the implementation of worship. Wudhu is used in normal conditions with water, while Tayamum is allowed in emergency conditions when water is not available or cannot be used. This finding underscores the principle of convenience (taysir) in Islamic teachings and emphasizes the importance of physical and mental cleanliness as the foundation of people's spirituality.